Effect of Internal and External Factors on Stock Price in Companies That Conduct Rights Issue - Riyanto, Feri Dwi; Habibie, Ahmad Farhan (JURNAL EKBIS, 2023)
This study aims to provide empirical evidence regarding the influence of internal factors (Rights issue, total assets, total liabilities) and external factors (world oil price, world gold price, exchange rate, fed interest rate) on stock prices in the capital market. This study used companies that conducted a Rights issue and were listed on the Indonesia Stock Exchange (IDX) from 2015 to 2021 with a total sample of 63 companies. The research method used is in the form of Generalized Least Square (GLS) analysis with white period weighting. Based on the results of each test, the study found that: 1) world oil prices have a significant influence on stock prices; 2) the Rights issue, exchange rate and interest rate of the Fed have a significant negative influence on the stock price; 3) total assets, total liabilities, and world gold price have no effect on stock prices.